E-040 Safety and performance of the neuroform atlasTM stent system in the treatment of intracranial aneurysms: a prospective, observational, multicentre, post-market european study (atlas EU PMCF study). (22nd July 2018) - Bonafé, A; Costalat, V; Schramm, P; Eckey, T; Barreau, X; Marnat, G; Piotin, M; Berlis, A; Weber, W; Zelenak, K; Narata, A; Hartmann, M; et al.
Abstract : Introduction: The study objective is to assess the safety and performance of Neuroform Atlas Stent in the treatment of intracranial aneurysms. The protocol allowed for use of all types of coils and adjunctive technologies as deemed appropriate by the participating investigators. The primary study endpoint is the permanent morbidity and mortality rate, defined as any major ipsilateral stroke or neurological death within 12 to 16 months following the procedure. The study is still ongoing. We present here a descriptive analysis of procedure feasibility, clinical safety and acute angiographic results. Methods: A total of 104 patients were included. Most patients were female (76%) with a mean age 55.1 year (SD=10.1). Sixteen patients (15%) had a prior (non-target) aneurysm treated. Most target aneurysms (n=82) were unruptured and elective cases (79.6%); 7 (6.8%) were symptomatic, and 9 (8.7%) were previously ruptured. Sixteen (15.5%) of target aneurysms had been previously treated. The size of aneurysms was <7 mm: 86 (84.3%), 7–12 mm: 13 (12.7%), >12 mm: 3 (2.9%). At baseline, 91 patients (87.5%) were symptom free (mRS=0), 11 mRS=1 and 2 mRS=2. Antiplatelet drugs were administrated prior, during and after the procedure according to each institution's protocol and under the supervision of each participating investigator. Results: A total of 129 Neuroform Atlas Stents were used in 104 patients (i.e. 2 stents in 20 patients, 3 and 4 stents each in one patient). In one patient, the stenting initially planned was abandoned. Major reason for using more than 2 stents was Y-stenting for bifurcation aneurysm. The stent was successfully implanted in 94.5% (121/128) of cases. The preferred coil delivery technique used was jailing (62.5%, n=65). Six procedural complications were observed including 2 in-stent thrombosis, 1 arterial occlusion, 1 access site complication, 1 contrast media encephalopathy and 1 perforation of the parent vessel. The latter event led to the patient death two days after the procedure. Upon the procedure, a complete aneurysm occlusion was observed in 69 patients (66.3%), residual neck and residual aneurysm were reported respectively in 22 (21.2%) and 13 (12.5%) patients. Mean time to discharge from hospital after the procedure was 3.29 days; none had undergone a re-intervention of target aneurysm at discharge. Eighteen patients (17.3%) experienced at least one adverse event between the procedure and discharge; 5 were serious, 12 of 22 events were not related to stent nor to the procedure. Acute clinical and angiographic assessments were self-reported. Conclusion: These interim results suggest that Neuroform Atlas Stent System is a safe device and permit adequate aneurysm embolization; Final study analysis will allow for assessing system effectiveness and long-term safety. Disclosures: A. Bonafé: 2; C; Stryker, Medtronic, MicroVention, Phenox, Balt. V. Costalat: 1; C; Stryker. 2; C; Medtronic, Balt, MicroVention, Stryker, Phenox. P. Schramm: 1; C; Siemens Healthineers, Penumbra. 2; C; Stryker, Penumbra. 3; C; Phenox, Cerenovus, Bracco, Bayer, Penumbra, Stryker, Siemens Healthineers. T. Eckey: 2; C; Stryker, Penumbra. X. Barreau: None. G. Marnat: None. M. Piotin: 2; C; Stryker, Medtronic, MicroVention, Balt, Penumbra. A. Berlis: 2; C; Stryker. W. Weber: 2; C; Medtronic, MicroVention, Xenon. 3; C; Penumbra, Stryker. K. Zelenak: None. A. Narata: None. M. Hartmann: 2; C; Stryker. J. Gentric: 2; C; Stryker. E. Houdart: 6; C; Stryker.